Bridging the cognitive-cellular neuroscience gap empirically: a study combining physiology, modelling and fMRI - Bickle, John; Avison, Malcolm; Schmithorst, Vincent; Landreth, Anthony; Holland, Scott (Journal of experimental & theoretical artificial intelligence, 2003)
Familiar questions about the relationship across levels separating psychology from the neurosciences have recently been mirrored in questions about the relationship across levels within the neurosciences themselves. How does 'cognitive neuroscience' relate to the discipline's current cellular and molecular mainstream? Here we adopt an empirical approach toward these 'levels' questions by describing our transdisciplinary research that incorporates findings from cellular physiology, neurocomputational modelling, and functional neuroimaging. Higher level investigations serve as-but only as-essential heuristics for discovering lower level mechanisms. This case study serves as an exemplar for transdisciplinary research in current and foreseeable neuroscience, and its lessons concerning the role of higher level investigations generalize to the more familiar 'levels' questions spanning cognitive science and the neurosciences.